2013
DOI: 10.7314/apjcp.2013.14.11.6919
|View full text |Cite
|
Sign up to set email alerts
|

The National "Smoking Cessation Clinics" Program in the Republic of Korea: Socioeconomic Status and Age Matter

Abstract: Multivariate logistic regression analyses were performed correcting for intra-class correlations within public health centers. Results: The overall 6-month quit rate was high (46.8%). Higher odds of smoking cessation were positively associated with higher levels of behavioral counseling sessions, but not nicotine replacement therapy (NRT). Cessation rates were lower for Medicaid participants than for regular health insurance participants. Disadvantaged younger smokers were less likely to participate in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Smokers in this phase were less likely to seek help from any quit smoking facilities. This finding is consistent with lower participation rate in younger smokers in smoking cessation programs held in local clinics (Kim et al, 2013), making them the neglected group of smokers for any smoking cessation intervention. Hence it is important to bring the intervention to workplace rather than waiting passively for the smokers to come to clinics.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Smokers in this phase were less likely to seek help from any quit smoking facilities. This finding is consistent with lower participation rate in younger smokers in smoking cessation programs held in local clinics (Kim et al, 2013), making them the neglected group of smokers for any smoking cessation intervention. Hence it is important to bring the intervention to workplace rather than waiting passively for the smokers to come to clinics.…”
Section: Discussionsupporting
confidence: 78%
“…Other studies from various parts of the world (Pierterse et al, 2001;Hilberink et al, 2005;Jayakrishnan et al, 2013;Kim et al, 2013) had showed better outcome with more counseling sessions, either in the form of telephone consultation, face-to-face interview, or group counseling. From the feedback of the participants in this study, similar brief counseling sessions either in the form of telephone consultation or face-to-face interviews were preferred because of the limited time off they get during working hours (limited to 15min in the morning, 45min lunch break, and another 15min at tea break).…”
Section: Discussionmentioning
confidence: 96%
“…Of the 12 articles, four have sample sizes of less than 30 [29][30][31][32], while two do not present the intervention results for the age group [33,34]. Of the remaining six, five focus on NRT [23,[35][36][37][38], with one that offers patients either NRT or bupropion [39].…”
Section: Identifying Optimal Smoking Cessation Pharmacotherapy For Olmentioning
confidence: 99%
“…In order to stimulate and aid smokers to quit, many different smoking cessation interventions have been developed and tested in different countries, such as face to face counselling of the person by a qualified health education professional, self-help materials, mass-media campaigns (Lancaster et al, 2000;Lancaster and Stead, 2005;van Keulen et al, 2011;Jayakrishnan et al, 2013;Kim et al, 2013;Paek et al, 2014;US Department of Health, 2014).…”
Section: Introductionmentioning
confidence: 99%